Acute pulmonary embolism in patients diagnosed at Emergency Department - Staśkiewicz, Grzegorz; Czekajska-Chehab, Elżbieta; Torres, Kamil; Chrościcki, Tomasz; Radej, Sebastian; Drop, Andrzej; Maciejewski, Ryszard (Polish Journal of Public Health, 2010)
Introduction. Acute pulmonary embolism is a frequent condition which may constitute an important diagnostic problem, especially in the setting of Emergency Department. Aim. The aim of the study was to analyze the time trend of the suspected pulmonary embolism in the setting of Emergency Department of the university hospital, as well as assess a yearly distribution of the number of examinations with suspected and confirmed pulmonary embolism. Material and methods. Radiology information system of the I Department of Radiology, Medical University of Lublin has been used to identify the patients with suspected pulmonary embolism diagnosed in the setting of the Emergency Department from 1 January 2007 to 31 December 2009. In the analyzed period, 420 multi-detector computed tomography pulmonary angiography examinations have been performed with pulmonary embolism suspected in the patients admitted to the Emergency Department of our institution. Results and conclusion. Mean confirmation rate was 34.8%. A significant increase (p